Students’ Perception on The Use of Readtheory.org at SMK Negeri 1 Suwawa - Nurlila Syayahni Syaripudin; Karmila Machmud; Sri Agriyanti Mestari (Transbahasa, 2025)
This research aims to explore students’ perceptions on the use of ReadTheory.org and how it affects their learning motivation in developing English reading skills. The study was conducted using a descriptive qualitative method involving five tenth-grade students from SMK Negeri 1 Suwawa. Data were collected through open-ended questionnaires and classroom observations during the students’ use of ReadTheory.org. The results indicate that students had positive perceptions toward the platform. They found ReadTheory.org engaging and helpful in improving their reading comprehension due to its adaptive features, immediate feedback, and varied reading topics. The platform also enhanced their learning motivation, as shown by increased enthusiasm, self-confidence, and independent study habits. Students reported feeling more motivated to read, were encouraged to improve their scores, and demonstrated perseverance in overcoming learning obstacles. Furthermore, teacher support played an important role in guiding students to use the platform effectively. In conclusion, the use of ReadTheory.org positively influenced students’ perceptions and motivation in reading English texts. The findings suggest that integrating digital tools like ReadTheory.org in the classroom can support technology-based reading instruction and foster students’ motivation, especially in vocational school contexts.